Simulation of single dual-band perturbed printed antenna - Esa, Mazlina; Ismail , M.K.H. (2003)
A single dual band rectangular microstrip antenna operating at L-band has been successfully designed and simulated. The design procedure starts from the formulation for the width dimension of the microstrip antenna. Upon achieving the most appropriate antenna width, the design proceeds to determining the most appropriate antenna length. The designed antenna is then simulated using a full wave electromagnetic simulation software. Analysis of one port characteristics is carried out on the designed antennas. The performance focuses on the return loss, input impedance, voltage standing wave ratio, current distribution and charge distribution. The designed antenna is then simulated with perturbed structures introduced. It is found that the antenna is well matched at its corresponding frequency of operations.